2011
DOI: 10.1016/j.febslet.2011.09.029
|View full text |Cite
|
Sign up to set email alerts
|

Human immunodeficiency virus-1 Nef suppresses Hsp70-mediated Tat activation

Abstract: Hsp70 physically interacts with Tat by anti tag coimmunoprecipitation (View interaction)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 33 publications
3
19
0
Order By: Relevance
“…Moreover, Hsp70 proteins mediate Tat activation and viral transcription, and are released in HIV-1 virions (4850). Both PSF and NONO bind the HIV-1 RNA instability element (INS), but only PSF causes a down-regulation of the Rev-dependent gag and env transcripts (51).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Hsp70 proteins mediate Tat activation and viral transcription, and are released in HIV-1 virions (4850). Both PSF and NONO bind the HIV-1 RNA instability element (INS), but only PSF causes a down-regulation of the Rev-dependent gag and env transcripts (51).…”
Section: Discussionmentioning
confidence: 99%
“…It is recently reported that Nef degrades Tat protein by the UPS (Sugiyama et al, 2011), which is crucial for an efficient virus replication, and counteracts the tetherin protein in SIVs, whose genomes lack vpu (Jia et al, 2009; Sauter et al, 2009; Serra-Moreno et al, 2013; Zhang et al, 2009). Further, it is reported that K144 in HIV-1 Nef is di-ubiquitinated for downregulation of CD4 and MHC-I (Cai et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…siRNA knockdown of Hsp70 resulted in activation of caspase-9 and caspase-3 (Behnsawy et al, 2011). Hsp70 has been shown during infection to modulate viral entry, transcription, translation, nuclear entry, and viron release (Halder et al, 2011; Sugiyama et al, 2011). A very recent study questioned the previous suggestion and indicated that Hsp70 may not have an IRES within its 5′ UTR (Sun et al, 2011).…”
Section: Cellular Ires-containing Genes and Their Roles In Er Stress mentioning
confidence: 99%